The determination of the biological function of bacterial pink pigment and Fusarium chlamydosporum on alfalfa (Medicago sativa L.) - Huang, Rong; Zhang, Hong; Chen, Haiyan; He, Linxin; Liu, Xiaoni; Zhang, Zhenfen (Frontiers in Microbiology, 2023)
Bacterial pigment is one of the secondary metabolites produced by bacteria, which has functions that are yet to be understood in relation to soil-borne pathogenic fungi in soil-borne pathogenic fungi and plants in mutualistic processes. After interacting with different concentrations of Cp2 pink pigment and Fusarium chlamydosporum, the study evaluates the growth, photosynthetic and physiological characteristics of alfalfa.The findings showed that Cp2 pink pigment has the ability to inhibit the growth of alfalfa, and the inhibition ratio gradually increased with the concentration increases. F. chlamydosporum inhibited the growth of alfalfa, which reduced photosynthetic physiological response and elevated antioxidant enzymes, is typically manifested by yellowing leaves and shortened roots. Under the combined effect of Cp2 pink pigment and F. chlamydosporum, as the concentration of Cp2 pink pigment increased, the inhibition of alfalfa displayed more severe symptoms and exhibited a more intense growth and physiological response. This indicates that Cp2 pink pigment is one of the potential virulence factors secreted Erwinia persicina strain Cp2, which play inhibitory accelerator in the interactions between F. chlamydosporum and alfalfa, have the potential to be developed into a plant immunomodulator agent.